2014
DOI: 10.1038/nn.3657
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of δ-catenin by DHHC5 mediates activity-induced synapse plasticity

Abstract: Synaptic cadherin adhesion complexes are known to be key regulators of synapse plasticity. However, the molecular mechanisms that coordinate activity-induced modifications in cadherin localization and adhesion and subsequent changes in synapse morphology and efficacy, remain unanswered. We demonstrate that the intracellular cadherin binding protein, δ-catenin, is transiently palmitoylated by DHHC5 following enhanced synaptic activity, and that palmitoylation increases δ-catenin/cadherin interactions at synapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
173
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(188 citation statements)
references
References 54 publications
(94 reference statements)
15
173
0
Order By: Relevance
“…Our results are consistent with data (27) that demonstrate that knockdown of ␦-catenin leads to a reduction in the activity induced stability of cadherin. Furthermore, Brigidi et al (27) demonstrated that knockdown of ␦-catenin perturbs chemically induced LTP-induced alterations in spine architecture in a cadherin-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with data (27) that demonstrate that knockdown of ␦-catenin leads to a reduction in the activity induced stability of cadherin. Furthermore, Brigidi et al (27) demonstrated that knockdown of ␦-catenin perturbs chemically induced LTP-induced alterations in spine architecture in a cadherin-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Brigidi et al (27) demonstrated that knockdown of ␦-catenin perturbs chemically induced LTP-induced alterations in spine architecture in a cadherin-dependent manner. Our data demonstrate that the reduction in head width and length induced by knockdown of ␦-catenin is independent of alterations in neural network activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delta-catenin has been shown to be palmitoylated in cultured hippocampal neurons, and disruption of the palmitoylation of delta-catenin decreases its association with N-cadherin. Interestingly, these authors identified two cysteines (C960 and C961) that are palmitoylated by the PAT DHHC5 (Brigidi et al, 2014). These cysteines are distinct from the conserved cysteine that we have identified in the plakophilins.…”
Section: Discussionmentioning
confidence: 60%